2017
DOI: 10.1039/c7ra00521k
|View full text |Cite
|
Sign up to set email alerts
|

Promotional effect of Ti doping on the ketonization of acetic acid over a CeO2 catalyst

Abstract: The promotional effect of Ti doping on the ketonization of acetic acid over a CeO2 catalyst was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The change of the lattice parameter of fluorite phase after addition of titanium and niobium confirms their incorporation into the fluorite structure ( Table 3 ). Since the doping cations Ti 4+ (0.74 Å) and Nb 5+ (0.74 Å) are smaller than cations of initial oxide Ce 4+ (0.97 Å) and Zr 4+ (0.84 Å) [ 24 ], the decrease of the cell parameter should be expected [ 25 , 26 , 27 ]. However, it unexpectedly increased after the addition of Ti and Nb.…”
Section: Resultsmentioning
confidence: 99%
“…The change of the lattice parameter of fluorite phase after addition of titanium and niobium confirms their incorporation into the fluorite structure ( Table 3 ). Since the doping cations Ti 4+ (0.74 Å) and Nb 5+ (0.74 Å) are smaller than cations of initial oxide Ce 4+ (0.97 Å) and Zr 4+ (0.84 Å) [ 24 ], the decrease of the cell parameter should be expected [ 25 , 26 , 27 ]. However, it unexpectedly increased after the addition of Ti and Nb.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Lu et al have for instance investigated the effect of Ti doping of CeO2 materials via a homogeneous precipitation method for the gas-phase ketonization of acetic acid at 280-350 °C. [106] An increased conversion was observed at all temperatures for Ti loadings of 10 and 30%, compared to both pure CeO2 and TiO2 parent materials, although a further increase to 50 and 70% was detrimental for the catalytic activity. Furthermore, the most active Ce0.7Ti0.3Ox material, the activity of which was also dependent on calcination temperature during synthesis, exhibited superior stability with time on stream compared to bare CeO2 for at least 8 hours.…”
Section: Catalyst Modificationmentioning
confidence: 87%
“…It is clearly seen that the desorption peaks, which represent Lewis basic sites and Brønsted acid sites were observed, indicating the coexistence of acidic and basic sites on the catalysts. 27,50 Brønsted acid sites mainly represented the surface hydroxyl groups and Lewis basic sites are corresponded to oxygen groups. From Fig.…”
Section: àmentioning
confidence: 99%
“…Hosni et al 24 synthesized Mg-Al-Ti LDHs containing divalent, trivalent and tetravalent cations, which was demonstrated as efficient visible-light photocatalysts. In the literature, 27 it was found that the activity and stability of Ce 1Àx Ti x O 2Àd catalysts were promoted by doping Ti content, which attributed to the enhanced redox properties together with the modication of surface acid-base sites, providing by the proper formation of Ce-O-Ti linkage bonds.…”
Section: Introductionmentioning
confidence: 99%